Rhizobium leguminosarum symbiovar viciae strains are natural wheat endophytes that can stimulate root development. (9th August 2022) - Bartoli, Claudia; Boivin, Stéphane; Marchetti, Marta; Gris, Carine; Gasciolli, Virginie; Gaston, Mégane; Auriac, Marie‐Christine; Debellé, Frédéric; Cottret, Ludovic; Carlier, Aurélien; Masson‐Boivin, Catherine; Lepetit, Marc; et al.
Abstract: Although rhizobia that establish a nitrogen‐fixing symbiosis with legumes are also known to promote growth in non‐legumes, studies on rhizobial associations with wheat roots are scarce. We searched for Rhizobium leguminosarum symbiovar viciae ( Rlv ) strains naturally competent to endophytically colonize wheat roots. We isolated 20 strains from surface‐sterilized wheat roots and found a low diversity of Rlv compared to that observed in the Rlv species complex. We tested the ability of a subset of these Rlv for wheat root colonization when co‐inoculated with other Rlv . Only a few strains, including those isolated from wheat roots, and one strain isolated from pea nodules, were efficient in colonizing roots in co‐inoculation conditions, while all the strains tested in single strain inoculation conditions were found to colonize the surface and interior of roots. Furthermore, Rlv strains isolated from wheat roots were able to stimulate root development and early arbuscular mycorrhizal fungi colonization. These responses were strain and host genotype dependent. Our results suggest that wheat can be an alternative host for Rlv ; nevertheless, there is a strong competition between Rlv strains for wheat root colonization. In addition, we showed that Rlv are endophytic wheat root bacteria with potential ability to modify wheat development.